Pengaruh Sistem Ta’awun Service Excelent dan Profesionalitas Terhadap Citra Lembaga Keuangan Syariah - Muhammad Ichan Kurniawan; Muhammad Irhan Arya Fathasyah; Muhammad Imam Syafa’at; Ade Akhmad Saputra (Ekonomis: Journal of Economics and Business, 2022)
The research carried out has the need to achieve the final results in order to gain knowledge about the effect of service excellent and professionalism on the image of sharia-based fund institutions. In Arabic, it can be seen that ta'awun is a word that has the meaning of helping. The mention of the word ta'awun is applied when an attitude or behavior is encountered to make it easier for others to participate in helping them. For the fulfillment of various living materials, each individual needs the help of other individuals by helping each other. To meet the needs of life, humans need the help of others by helping each other. It is even known that there are only a few people who refuse to apply the nature of Ta'awun in living the day. The research method used in this research is a library study method or a method that uses various written sources from the library. The collection of data and information is done through various written sources, such as books, articles, and other library sources. Starting from the title, abstract, core, and discussion using literature. The results of the study were carried out with related descriptions from the results of the study of literature, books and from internet sources. The results of the study found that the examples of Ta'awun related to the human condition were very limited.